The comparative African regional economics of globalization in financial allocation efficiency: The pre-crisis era revisited - Simplice Asongu; Joseph Nnanna; Vanessa Tchamyou (Financial Innovation, 2020)
This study assesses the role of globalization-fueled regionalization policies on the financial allocation efficiency of four economic and monetary regions in Africa from 1980 to 2008. Banking and financial system efficiency proxies are used as dependent variables and seven bundled and unbundled globalization variables are employed as independent indicators. The bundling is achieved by principal component analysis, while the empirical evidence is based on interactive fixed effects regressions. The findings are as follows. First, financial allocation efficiency is more sensitive to financial openness compared to trade openness and most sensitive to globalization. The relationship between allocation efficiency and globalization-fueled regionalization policies is defined by: (i) a Kuznets or inverted U-shaped curve in the UEMOA and CEMAC zones (evidence of decreasing returns for allocation efficiency from globalization-fueled regionalization) and (ii) a U-shaped relationship overwhelmingly in the COMESA and scantily in the EAC (increasing returns to allocation efficiency due to globalization-fueled regionalization). These relationships are relevant to the specific globalization dynamics within regions. Economic and monetary regions are more prone to surplus liquidity than pure economic regions are. Policy implications and measures for reducing surplus liquidity are also discussed.
Keywords: A10; D60; E40; O10; P50; 650; Globalization; Financial development; Regional integration; Panel; Africa